2021
DOI: 10.1002/mgg3.1770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel MITF mutations in Chinese families with Waardenburg syndrome type II

Abstract: Background Waardenburg syndrome (WS) is a rare autosomal‐dominant syndrome and is characterized by sensorineural hearing loss and pigment abnormalities. It is subdivided into four types according to the clinical characteristics. MITF is one of the major pathogenic genes for type II. The aim of this study was to investigate MITF mutations and the clinical characteristics of WS type 2 (WS2) in four Chinese families. Method Clinical diagnoses were based on detailed clinical findings. Six WS2 patients from four un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The application of various genetic screening techniques, including whole-genome sequencing (WGS) and exome sequencing, has facilitated the precise diagnosis of numerous genetic diseases caused by rare variants. [18][19][20][21][22][23][24][25] For instance, an exome sequencing study on an Indian family identified a rare deleterious homozygous missense variant in the RXFP2 gene, which causes cryptorchidism. 26 Although exome sequencing is more commonly used than WGS due to its lower cost, WGS offers a more uniform distribution of sequencing quality (including single-nucleotide variants, insertions and deletions) and a higher discovery rate of coding-region variants, approximately 3%.…”
Section: Novel Disease Locimentioning
confidence: 99%
“…The application of various genetic screening techniques, including whole-genome sequencing (WGS) and exome sequencing, has facilitated the precise diagnosis of numerous genetic diseases caused by rare variants. [18][19][20][21][22][23][24][25] For instance, an exome sequencing study on an Indian family identified a rare deleterious homozygous missense variant in the RXFP2 gene, which causes cryptorchidism. 26 Although exome sequencing is more commonly used than WGS due to its lower cost, WGS offers a more uniform distribution of sequencing quality (including single-nucleotide variants, insertions and deletions) and a higher discovery rate of coding-region variants, approximately 3%.…”
Section: Novel Disease Locimentioning
confidence: 99%
“…The application of various genetic screening techniques, including wholegenome and exome sequencing (WGS/WES), has facilitated the precise diagnosis of numerous genetic diseases caused by rare variants [18][19][20][21][22][23][24][25] . For instance, a WES study on an Indian family identified a rare deleterious homozygous missense variant in the RXFP2 gene, which causes cryptorchidism 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The high mutation prevalence of MITF in Chinese WS patients has been deeply concerning (Li et al, 2019;Wang et al, 2022). Based on clinical findings, WS patients with MITF mutations usually show complete expression of possible symptoms, such as severe congenital SNHL, extensive skin hypopigmentation, and complete heterochromia iridum (Song et al, 2016;Wang et al, 2018Wang et al, , 2021. Despite the comprehensive investigation in animal models, the pathogenic mechanism of mutated MITF is still poorly described in humans (Chen et al, 2020;Du et al, 2019;Ni et al, 2013;Steingrímsson et al, 1994;Tachibana et al, 2003).…”
Section: Introductionmentioning
confidence: 99%